KETERAMPILAN BERPIKIR KRITIS DAN PENGAJARANNYA DI SEKOLAH DASAR - Novandi, Mas; Serani, Gabriel; Djudin, Tomo; Suratman, Dede (STKIP Persada Khatulistiwa Sintang, 2025)
Critical thinking skills are an essential element of 21st-century education that must be developed from the elementary level. However, the teaching of these skills in primary schools still faces various challenges. This literature review aims to analyze the concept of critical thinking, its importance for elementary students, and effective teaching strategies within the context of science education. The study employs a systematic literature review method by analyzing theories from critical thinking experts such as Ennis, Beyer, Glaser, Paul and Elder, and Facione. The findings indicate that critical thinking involves the abilities of interpretation, analysis, evaluation, and inference, and is influenced by students’ intellectual dispositions. The importance of critical thinking at the elementary level is supported by numerous studies that show its role in enhancing conceptual understanding, creativity, and problem-solving abilities. Effective teaching strategies include question-based learning, classroom discussions, the use of technology, and inquiry-based approaches in science instruction. This study recommends that critical thinking instruction be integrated into the elementary school curriculum using approaches aligned with students’ cognitive development stages.